Created equal : Clarence Thomas in his own words - Pack, Michael; Paoletta, Mark (Regnery Publishing, 2022)
Although Clarence Thomas remains a controversial figure, few know him beyond his contentious confirmation battle. But beyond the headlines, Thomas' life is a classic American tale; born poor in the segregated South, only to become one of the most influential justices in the highest court in the land. In the follow-up to the wildly successful documentary by the same name, Created Equal builds on dozens of hours of groundbreaking, one-on-one interviews with Thomas to share a new, expanded account of his powerful story for the first time.